Gender and the Book Trades : - Farrell-Jobst, Jessica; Watson, Elise (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
This volume proposes a new and radically inclusive approach to the study of the book by using gender as a tool of analysis. While female authors and women in the book trades have long been studied, gender itself has yet to be explored as a methodology rather than a subject in book history. We argue that putting gender analysis into practice requires thinking inclusively about both the book world and the interactions of its participants from the beginning. With twenty-five pioneering case studies that stretch from colonial Peru to modern Delhi, using a variety of intersectional methodologies including network analysis, critical bibliography, and queer theory, Gender and the Book Trades sets out an innovative method of analysing the printed book. Contributors include: Rebecca Baumann, Montserrat Cachero, Verônica Calsoni Lima, Matthew Chambers, Kanupriya Dhingra, Nora Epstein, Natalia Fantetti, Jessica Farrell-Jobst, Agnes Gehbald, Rabia Gregory, Laura Guinot Ferri, Elizabeth Le Roux, Sarah Lubelski, Natalia Maillard Álvarez, Charley Matthews, Susan McElrath, Kirk Melnikoff, Malcolm Noble, Kate Ozment, Joanna Rozendaal, Kandice Sharren, Valentina Sonzini, Elise Watson, Joëlle Weis, Helen Williams, Alexandra E. Wingate, and Georgianna Ziegler.